Stigmatizing attitudes and misconceptions about obesity among Spanish healthcare professionals - David Sánchez-Carracedo; Albert Fornieles-Deu; Dimitra Anastasiadou; Stuart W. Flint (PLoS ONE, 2026)
Weight stigma and misconceptions about obesity among healthcare professionals (HCPs) may negatively affect healthcare quality and access for people living with obesity (PLWO). However, no previous research has examined these attitudes and beliefs in Spanish HCPs. This cross-sectional online study examined weight stigma and obesity-related beliefs among 922 HCPs recruited via Spanish professional and academic obesity-related organizations ((74.1% female, mean BMI = 23.73 kg/m 2 (SD 3.89), mean age = 43.73 years (SD 12.45), range 23–75, 88.7% provide care for PLWO)). Anti-fat attitudes were measured using the Dislike subscale of the Anti-Fat Attitudes questionnaire (AFA) and the Fat Phobia Scale (F-Scale). ANOVAs adjusted for sociodemographic variables, weight status, and weight bias internalization were conducted. Overall, Spanish HCPs surveyed reported negative attitudes toward PLWO. Lower weight status was consistently associated with higher stigma scores. Younger age (F-Scale) and working in the private sector (Dislike) were associated with higher scores. Differences across specialties were observed, with obesity physicians reporting the lower stigma levels. A substantial proportion of HCPs endorsed beliefs emphasizing personal responsibility: 38% attributed overeating to individual causes, 66% believed obesity could be entirely prevented by a healthy lifestyle, and 59% believed it could be cured through lifestyle changes. Many also attributed weight loss difficulties, poor compliance, and weight regain to lack of motivation and lifestyle choices, and over half considered lifestyle or psychological interventions the most effective treatment for severe obesity. Endorsement of these beliefs was consistently associated with higher stigma scores. These findings provide national evidence that weight stigma among Spanish HCPs is present and linked to beliefs framing obesity as primarily under individual control. These attitudes and knowledge gaps may contribute to inappropriate care and unfair treatment of PLWO. Addressing responsibility-focused beliefs may be a key step towards reducing stigma and improving the quality of obesity care in Spain.